1975
DOI: 10.1002/art.1780180608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complement and polymorphonuclear leukocyte depletion on experimental skin lesions resembling systemic lupus erythematosus

Abstract: Immunopathologic cutaneous lesions resembling human systemic lupus erythematosus (SLE) can be induced in mice sensitized to ultraviolet (UV)-irradiated DNA following whole body irradiation with UV light. The lesions are characterized by the formation of immune complexes at different skin sites. The role played by cellular and humoral mediators in the pathogenesis of this experimental model was investigated. The results obtained suggest that inflammation that follows UV radiation is the major factor responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…We suspect that the reduction in serum complement system activity at 8 and 16 hr per day of artificial UV/visible light demonstrates a UVA‐B dose‐dependent response, which might affect the IS of captive herpetofauna. Similar reports were obtained in mice using experimental skin lesions, in which long UVR is the major factor responsible for this pathology [Natali et al, ]. Up to now, the details of how UV exposure may suppress the immune responses have not been elucidated.…”
Section: Discussionsupporting
confidence: 67%
“…We suspect that the reduction in serum complement system activity at 8 and 16 hr per day of artificial UV/visible light demonstrates a UVA‐B dose‐dependent response, which might affect the IS of captive herpetofauna. Similar reports were obtained in mice using experimental skin lesions, in which long UVR is the major factor responsible for this pathology [Natali et al, ]. Up to now, the details of how UV exposure may suppress the immune responses have not been elucidated.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study using a single high dose of UVB irradiation on WT mice revealed transient proteinuria, accompanied by the transmigration of neutrophils from the inflamed skin to the kidneys, as monitored by a photoactivatable lineage tracking approach ( 31 ), highlighting the potential dermal-renal crosstalk in response to the acute skin injury. In addition, a previous study demonstrated that neutrophil depletion protects mice from developing UV-irradiation-induced lupus-like skin lesions ( 42 ). On the other hand, skin infection by staphylococcal aureus in Nfkbiz ΔK5 mice promotes keratinocyte apoptosis, neutrophil activation and NET release, leading to SLE-like autoimmune inflammation and kidney injury ( 32 ).…”
Section: Discussionmentioning
confidence: 99%